SMALL FARMS IN THE AREA STRUCTURE OF AGRICULTURAL HOLDINGS OF THE EUROPEAN UNION COUNTRIES - Strojny, Jacek (Acta Scientiarum Polonorum. Oeconomia, 2020)
In spite of the evolution of the agrarian structure in EU countries (particularly in Western Europe) the problem of small agricultural holdings is still relevant, as this form of farming remains functional. The term ‘small farm’ has an ambiguous character. Thus, the study is based on relatively the most objective criterion for identification of small holdings – farms covering areas below 5 ha. The study employs the statistical method of vector elimination, which enables separation of subgroups with similar, homogeneous agrarian structures from among the studied set. The typology of the agrarian structure by means of the taxonomic technique demonstrates how diverse EU countries are with regard to their small agricultural holdings: Southern European countries, some Central European countries, and other states lying in the north of Europe. Additionally, the structure of small agricultural holdings is distinct in Denmark and in the Czech Republic.